Integrated enterprise resource planning (ERP) perception to use for decision making purpose in higher education institutions in Nigeria - Aremu, Adejare Yusuff (2015)
The summary review of this research study it is as follow here, the main purpose of this work paper is to analysis the factor that affect the Integrated of Enterprise Resource Planning (ERP) in the purpose of perception to use ERP for decision making in higher education institutions in Nigeria. There are some factors that examined in this research work, which are: ERP Life Cycle development, Characterizing achievement, Enterprise system experience, ERP Implementation in HEIs, Organizational Theory Applications, ERP system in higher education, etc. Quantitative data was ensured for this study, and Nigeria higher education workers bark home was used as respondent in this work, a structured questionnaire survey was used to collect data from the respondents which are Masters and Phd final year student of UUM, USM and UNIMAP are using as the respondent for this study, which they're workers of various higher education institutions in Nigeria. Eleven different departments were selected and the population sampling focus is 200, which 85 Questionnaires were distributed and collected bark after respondent answered is 73 except 12 oncollected. SPSS and PLS were used for data analysis, Also Reliability and Validity instrument were tested. Tam model were using to test the believed of staffs of HEIs in Nigeria based on this seven components, Quality of internet connection, Ease of used, ERP Feeling enjoyment, Security and Privacy, Usefulness, Amount of information and perception to use Em. Also Regression and Correlation were analysis and lastly, relevant hypotheses was derived and tested by using PLS software, where three variables are rejected and three are supported. The contribution of this study to HEIs in Nigeria is to reducing the operational cost, save time, to provided student ease accessing online group discussion and improvement in term of learning quality.